2014
DOI: 10.1002/adma.201304428
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Crowding Meets Tissue Engineering by Self‐Assembly: A Paradigm Shift in Regenerative Medicine

Abstract: MMC, the addition of inert polydispersed macromolecules in the culture media, effectively emulates the dense in vivo extracellular space, resulting in amplified deposition of ECM in vitro and subsequent production of cohesive, ECM-rich living substitutes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 155 publications
(137 citation statements)
references
References 83 publications
6
124
0
Order By: Relevance
“…This is in accordance to previous studies that demonstrated that negatively charged macromolecules (e.g. DxS and CR) accelerate tissuespecific ECM deposition, recognising CR as the most effective crowder, due to its inherent polydispersity that achieves more effective volume occupancy / exclusion and thus higher ECM deposition (40). ICC analysis demonstrated that HCFs were negative for α SMA, CD34 and keratocan.…”
Section: Page 17 Of 56supporting
confidence: 91%
See 2 more Smart Citations
“…This is in accordance to previous studies that demonstrated that negatively charged macromolecules (e.g. DxS and CR) accelerate tissuespecific ECM deposition, recognising CR as the most effective crowder, due to its inherent polydispersity that achieves more effective volume occupancy / exclusion and thus higher ECM deposition (40). ICC analysis demonstrated that HCFs were negative for α SMA, CD34 and keratocan.…”
Section: Page 17 Of 56supporting
confidence: 91%
“…The medium was replaced after 24 h with fresh medium containing the optimum concentration of macromolecular crowders (100 µg/ml of DxS or 75 µg/ml of CR; both negatively charged) (40,41) with various concentrations of newborn calf serum (NBCS) or human serum (HS), ranging from 0.0 to 10 %. 100 µM L-ascorbic acid phosphate supplement was added in the medium to enhance collagen synthesis.…”
Section: Macromolecular Crowdingmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the addition of negatively charged macromolecules in the culture media (Figure 6), by imitating the naturally crowded in vivo context, dramatically accelerates the conversion of procollagen to collagen, resulting in a 30-to 80-fold increase in tissue-specific ECM deposition. Using human TCs, a rich in ECM and cohesive cell-sheet was produced with intact cell-cell and cell-ECM junctions as early as 6 days in culture, without any negative effects in TC functions [449]. Despite these advancements, a complete threedimensional tendon-equivalent has yet to be developed.…”
Section: Tissue Engineering By Self-assembly Therapiesmentioning
confidence: 99%
“…Further, such approaches require prolonged in vitro culture to develop a proper 3D model, which is often associated with cell phenotypic drift [137,138]. Although macromolecular crowding aspires to address this slow or delayed ECM deposition [139][140][141], this technology is still at the primitive stages and, for that reason, scaffoldbased technologies (e.g., hydrogels, fibres, sponges) are under intense investigation.…”
Section: Decellularised Tissues and Cell Layersmentioning
confidence: 99%